Circadian and Sleep Dysfunctions in Neurodegenerative Disorders—An Update - Fifel, Karim; Videnovic, Aleksandar (Frontiers in Neuroscience, 2021)
Disruptions of sleep and circadian rhythms are among the most debilitating symptoms in patients with neurodegenerative diseases. Their underlying pathophysiology is multilayered and multifactorial. Recent evidence suggests that sleep and circadian disturbances may influence the neurodegenerative processes as well as be their consequence. In this perspective, we provide an update of the current understanding of sleep and circadian dysregulation in Alzheimer’s, Parkinson’s, and Huntington’s diseases.